Exploring the role of the "Big Three" features of effective youth development programs in El Salvador: The sample case of programs of Compassion International. (November 2021) - Tirrell, Jonathan M.; Hay, Samuel W.; Gansert, Patricia K.; Le, Trang U.; O'Neil, Bridget C.; Vaughn, Jennifer M.; Bishara, Leanne; Tan, Esther; Lerner, Jacqueline V.; King, Pamela Ebstyne; Dowling, Elizabeth M.; Williams, Kate; et al.
Programs effective in promoting positive youth development (PYD) involve curricular features termed the Big Three: Positive and sustained adult–youth relationships; life-skill-building activities; and youth contribution and leadership opportunities. Data from 610 adolescents (50% female; M age = 16.39 years, SD = 1.83) enrolled in Compassion International-supported programs in El Salvador indicated that scores derived from a youth-report measure of the Big Three, established using data from Rwanda, manifested strong invariance and predicted both youth strengths and contribution. Qualitative interviews with 18 youth from these programs indicated that the Big Three were seen as present and enhancing their positive development. We discuss how future research using a quantitative–qualitative approach may provide deeper evidence about the practical application and promotion of PYD in youth programs.